Evolution of Solar Wind Turbulence during Radial Alignment of Parker Solar Probe and Solar Orbiter in 2022 December - Ashok Silwal; Lingling Zhao; Xingyu Zhu; Luca Sorriso-Valvo; Lina Z. Hadid; Gary P. Zank; Hui Li; Samuel T. Badman; Yeimy J. Rivera; Sujan Prasad Gautam; Monika Karki; Juan G Alonso Guzman; et al. (The Astrophysical Journal Supplement Series)
We investigate the radial evolution of solar wind turbulence during the radial alignment of Parker Solar Probe (PSP) and Solar Orbiter (SO) on 2022 December 10, with PSP located at approximately 0.11 au and SO near 0.88 au. To identify nearly the same plasma parcel crossing both spacecraft, we apply a ballistic propagation model with time-constant acceleration constrained by in situ solar wind velocity measurements at PSP and SO. We trace the magnetic footpoint of the plasma parcel back to the photosphere using a potential field source surface model based on a Global Oscillations Network Group synoptic magnetogram. Field and plasma measurements from PSP and SO are used to analyze power spectral density (PSD), spectral scaling, magnetic compressibility, and intermittency. Our results show that (1) the trace PSD of magnetic fluctuations steepens in the inertial range and flattens in the dissipation range with increasing radial distance; (2) the spectral break shifts to lower frequencies at SO; and (3) the Castaing model reveals multifractal intermittency in the inertial range, with slightly weaker intermittency at SO. These findings based on the same plasma parcel are consistent with the results of statistical studies on the radial evolution of turbulence and provide a reference for theoretical modeling of turbulence in the inner heliosphere.